(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
This study investigates the preferred learning styles of polytechnic students in Nigeria and their impact on academic performance in mathematics. Using a quantitative survey design, 500 National Diploma One (ND 1) students from Plateau State Polytechnic, Barkin Ladi, and Isa Mustapha Agwai Polytechnic, Lafia were sampled. Data were collected through the Perceptual Learning Style Preference Questionnaire (PLSPQ) and students’ academic records. Descriptive statistics and Pearson correlation and analysis of variance (ANOVA) were used for data analysis. The study found that auditory and visual learning styles were most preferred and had a statistically significant relationship with students’ mathematics performance. Gender differences were also found to significantly influence performance, whereas institutional affiliation had no significant effect. Based on these findings, the study recommends the integration of multimodal teaching methods to enhance mathematics instruction and support diverse learning needs in polytechnics.